Exploring the relationship between functional movement competence, stroke technique and competitive swimming performance in both elite and amateur swimmers - Oguz, H.; Rolt, C.; Nolte, K.; Bathgate, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Aim: The Functional Movement Analysis (FMA) is a grading system which theoretically screens movement patterns and provides quantitative data about the mechanics of the musculoskeletal system during the execution of a motor task, whereas swimming performance is evaluated in terms of performance times and technique analysis. The primary objective of this study was to explore the relationship between functional movement screen competence and swim stroke technique, with a secondary objective of determining whether these scores are correlated with swimming competition performance, in both elite and amateur swimmers. Methods: Twenty six male and female swimmers (ELITE, n=12; and AMATEUR, n=14) took part in the study. There were two test days each separated by 24 hours. On test day one, 2D video analysis was used to record each swimmer`s functional movement ability, which included movements that test trunk stability, overhead squat, rotational stability and shoulder external rotation. The third attempt of each movement was used in analysis. On test day two, underwater 2D video analysis was used to collect 100m freestyle swim from each swimmer which was later used for analysis. Three subdivisions were used; body position in the water, stroke analysis and kick analysis on both the right and left side of the swimmer, and scored using the USA stroke technique score card. Finally each swimmer`s competitive performance was determined by the FINA points received for best race swam in that current year. Results: Right and Left side stroke analysis scores significantly correlated with trunk stability FMA score (r=0.383 & r=0.419 for right and left side respectively, p<0.05). Right side kick analysis significantly correlated to the swimmers right side shoulder external rotation (r=0.407, p<0.05), however the correlation was not strong enough on the left to be significant. Right and left side body position scores from the swim analysis showed no significant correlation with any of the functional movements tested. No significant correlations were found between the swimmers competitive performance scores, and their function movement overall scores, however there were significant positive correlations with right and left side stroke analysis scores. Conclusion: The results indicate that problems identified in a swimmers stroke could be rectified by improving swimmers trunk stability. From this study we cannot reveal that a poor functional movement score will determine a poor performance in the pool, and or vice versa. However, future research is recommended to investigate these correlations further with a larger subject pool, to enhance the relationships found within certain functional movements and stroke analysis which showed weaker correlations which perhaps could be further linked with performance output.